Perancangan Furnitur untuk Villa di Lingkungan Tropis - Kevin Leonardo; Adi Santosa (Intra, 2016)
Progressive advance of modern lifestyle demands people to drown in their hectic work life and made them forget about the need to rest. One of human basic needs to take a rest is relaxing. Villa is one of the place which supports that kind of activities, especially in tropical environments, so this villa furniture design is intended to accommodate relaxation activity, through solving the solution of tropical environment Issues raised from the tropical environment are issues about high temperatures and humidity , which can be solved through a perforated surface formations, as well as the use of natural materials which grows in tropical environment itself, which are coconut wood and rattan. Beside material and shape aspects, it is also preferred to apply ergonomic dimensions in detail to support comfort in use, so the purpose of the relaxation itself can be achieved. This design is supported with field observations, environment and ergonomics analysis as well as offset by the supporting literature, so this design is capable of supporting the relaxation function more optimally.